An efficient k-means clustering algorithms: Analysis and implementation - Kanungo, Tapas; Mount, David M; Netanyahu, Nathan S; Piatko, Christine D; Silverman, Ruth; Wu, Angela Y (IEEE transactions on pattern analysis and machine intelligence, 2002)
In k-means clustering, we are given a set of n data points in d-dimensional space R super(d) and an integer k and the problem is to determine a set of k points in R super(d), called centers, so as to minimize the mean squared distance from each data point to its nearest center. A popular heuristic for k-means clustering is Lloyd's algorithm. In this paper, we present a simple and efficient implementation of Lloyd's k-means clustering algorithm, which we call the filtering algorithm. This algorithm is easy to implement, requiring a kd-tree as the only major data structure. We establish the practical efficiency of the filtering algorithm in two ways. First, we present a data-sensitive analysis of the algorithm's running time, which allows that the algorithm runs faster as the separation between clusters increases. Second, we present a number of empirical studies both on synthetically generated data and on real data sets from applications in color quantization, data compression, and image segmentation.